2012
DOI: 10.4049/jimmunol.1103505
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-494 Is Required for the Accumulation and Functions of Tumor-Expanded Myeloid-Derived Suppressor Cells via Targeting of PTEN

Abstract: Myeloid-derived suppressor cells (MDSCs) potently suppress the anti-tumor immune responses and also orchestrate the tumor microenvironment that favors tumor angiogenesis and metastasis. The molecular networks regulating the accumulation and functions of tumor-expanded MDSCs are largely unknown. In this study, we identified microRNA-494 (miR-494), whose expression was dramatically induced by tumor-derived factors, as an essential player in regulating the accumulation and activity of MDSCs by targeting of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
220
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(230 citation statements)
references
References 49 publications
9
220
0
1
Order By: Relevance
“…In addition, miR-494 enhances myocyte survival by targeting PTEN, ROCK1, and CAMKIId and protects against ischemia/reperfusion-induced cardiac injury (29). miR-494 is also an essential player in regulating the accumulation and activity of myeloidderived suppressor cells by targeting PTEN and activation of the Akt pathway (25). We confirmed a direct connection of PED S104G overexpression and down-regulation of miR-494.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, miR-494 enhances myocyte survival by targeting PTEN, ROCK1, and CAMKIId and protects against ischemia/reperfusion-induced cardiac injury (29). miR-494 is also an essential player in regulating the accumulation and activity of myeloidderived suppressor cells by targeting PTEN and activation of the Akt pathway (25). We confirmed a direct connection of PED S104G overexpression and down-regulation of miR-494.…”
Section: Discussionsupporting
confidence: 71%
“…It has recently been shown that miR-494 has an important role in tumor progression in myeloid-derived suppressor cells by targeting phosphatase and tensin homolog (PTEN) (25). As a result, we wondered if miR-494 could also have a role in tumorigenicity of NSCLC.…”
Section: Resultsmentioning
confidence: 99%
“…Further, miR-223 was found to negatively regulate progenitor proliferation, granulocyte differentiation, and activation in a MEF2C-dependent manner (60). miR-494 expression induced by tumor-derived TGF-␤1 was shown to play a critical role in the regulation of accumulation and function of tumor-expanded MDSCs by specifically targeting PTEN (61). miR-17-5p and miR-20a could decrease the expression of reactive oxygen species and suppressive function of tumor-induced MDSCs by targeting Stat3 (62).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1 ϫ 10 4 HEK-293 cells were seeded onto 96-well plates and incubated overnight. jetSI-ENDO transfection reagents (Polyplus-transfection, Illkirch, France) were used for the cotransfection of plasmids and RNAs as we described previously (44). Thioglycollate-elicited mouse peritoneal macrophages were prepared and cultured as described previously (45).…”
Section: Methodsmentioning
confidence: 99%